STRATEGIES FOR DEVELOPING STUDENTS’ ACADEMIC WRITING SKILLS IN FOREIGN LANGUAGE TEACHING: STRATEGIES FOR DEVELOPING STUDENTS’ ACADEMIC WRITING SKILLS IN FOREIGN LANGUAGE TEACHING - Tazbulatova, Gulzhannat (Журнал иностранных языков и лингвистики, 2025)
list of required documents, such as filling out forms, writing a motivation letter, providing several letters of recommendation and other, depending on the university. “Academic transcripts from previous study including grade scale and English translation if originals are in another language, Proof of English language proficiency